Efektivitas Kebijakan Perlindungan Data Pribadi dalam Menjaga Hak Asasi Manusia di Era Teknologi di Indonesia - Judijanto, Loso; Lubis, Arief Fahmi; Sam Karauwan, Donny Eddy; Bungin, Sator Sapan; Mau, Hedwig Adianto (Sanskara Hukum dan HAM, 2024)
This research investigates the effectiveness of personal data protection policies in protecting human rights in the context of the technological era in Indonesia, using normative juridical analysis. The rapid advancement of digital technology has raised concerns regarding personal data protection, which directly impacts individuals' rights to privacy and freedom from exploitation. This research critically examines Indonesia's existing legal framework, including key regulations and the Personal Data Protection Bill, and assesses its alignment with international standards such as the GDPR. It identifies significant gaps and challenges in the current legal framework, including issues relating to law enforcement, public awareness, and the rapid pace of technological change. The findings suggest that while Indonesia has made progress in building a legal foundation for data protection, further improvements are needed to ensure robust protection for human rights in the digital age. The study concludes with recommendations to improve legal mechanisms to better protect individual rights in an ever-evolving technological landscape.